Dual Quasi-Bound States in the Continuum Modes for Optical Activity Manipulation - Dongfang Shen (IEEE, 2021)
Quasi-bound states in the continuum (quasi-BIC) are a particular resonant state, which can be regulated by the degree of symmetry breaking in nanostructures. Here, we propose a fourfold rotationally symmetric (C4v) metasurface supporting the dual quasi-BIC modes. The Fano characteristics have observed in the near-infrared region. The resonant peaks of the dual quasi-BIC modes can be adjusted flexibly and independently with a simple breaking of the structural symmetry. More importantly, the dual quasi-BIC modes demonstrate the extraordinary capability in controlling the optical activity. This work will offer us more freedom for controlling the resonance and optical activity by the quasi-BIC modes, which is promising to engineer the optical device in displaying and optics communications.